|English Pronouns||Arabic Pronouns||Perfect||Imperfect|
|You two (m,f)||antumaa||akaltumaa||ta'kulaani|
|They two (m)||humaa||akalaa||ya'kulaani|
|They two (f)||humaa||akalataa||ya'kulaani|
Click here to see more verb conjugations
In the Arabic grammar, the verbs are represented by the singular third person masculine. In English, we say, "to eat" to represent the "verb form". In Arabic, it is represented with the "he ate", e.g., third person singular masculine. So, this gives a leverage to the learner of the Arabic language. As soon as one laerns the verb form, one already knows how to make a complete sentence, e.g. "akala" (the verb under the "perfect" column corresponding to the pronoun "He" from the table above.) It means, "He ate". A complete sentence.
Okay. Let's make little more progress to tackle how to generate other forms
of the verb for all persons from the third person masculine singuler 'He".
In Arabic, the verbs usually are represented by three letters. The three letter form is called the "root" form of the verb. E.g., in the above example, the root form of the "eat", "akala" is the three letters which form the "akala". These three letters are: "a-ka-la," e.g., the first letter is alif=a, (see the above transliteration table), the middle letter is ka=k=kaaf, and the third letter is la=l=laam. Thus, the root form of the akala is three letters, a-k-l. Every other form is generated from this three letter root form. E.g., we add suffixes and prefixes to the root form to generate other tenses and forms. In order to produce the perfect tense forms of the verbs, we first take the three letter root form of the verb and throw the "haraka" of the last letter, e.g., in the case of "akala" we throw out the last "a" from it. What is left is the "akal". We add suffixes to the "akal" to produce the other pronouns. For example, for the first person singular, i.e., "I" we add the suffix "-tu" e.g., now it becomes "akal-tu" = akaltu = I ate.
Let's list the suffixes for all the pronouns now.
I = -tu
thou (masc) = -ta
thou (fem) = -ti
he = root form
she = -at
we = -naa
you (masc) = -tum
you (fem) = -tunna
they (masc) = -uu
they (fem) = -na
Okay. Let's look at the table above to see the final results after the suffixes are added to the root "akal". It was very easy, isn't it?
Let's go over again.
the root was "akal" after throwing the last "a" from "akala".
Add the suffix -tu to form for the pronoun "I". It becomes, akal-tu=akaltu= I ate.
Add the suffix -ta to form for the pronoun "Thou-masc". It becomes, akal-ta=akalta= Thou ate (masc).
Add the suffix -ti to form for the pronoun "Thou-fem". It becomes, akal-ti=akalti= Thou ate (fem).
No addition to the root form for the "He". It is the root form "akala."
Add the suffix -at to form for the pronoun "She". It becomes, akal-at=akalat= she ate.
Add the suffix -naa to form for the pronoun "we". It becomes, akal-naa=akalnaa= We ate.
Add the suffix -tum to form for the pronoun "you -plural masc". It becomes, akal-tum=akaltum= You ate (masc).
Add the suffix -tunna to form for the pronoun "You -plural fem". It becomes, akal-tunna=akaltunna= You ate (fem).
Add the suffix -uu to form for the pronoun "They -plural masc". It becomes, akal-uu=akaluu= They ate (masc).
Add the suffix -na to form for the pronoun "They -plural fem". It becomes, akal-na=akalna= They ate (fem).
I am sure you can figure out the forms for the "dual" or "plural two persons" from the table and the discussion above.